Planning for the telecommunications-based city: experience and prospects - GRAHAM, Stephen (European Spatial Research and Policy, 1994)
This paper analyses the experience in applying 'telematics' networks and services to confront the urban policy and planning challenges facing cities. Telematics - the result of the convergence of telecommunications and computing technologies - are important facilitating technologies behind current processes of urban restructuring. But they are also a prime focus of current urban policy innovation. Three particular areas of such innovation are discussed in this paper: using telematics for urban economic development, developing social and community telematics applications, and networking between different cities. A wide range of policy experience is analysed in each area. The paper concludes by highlighting the continued importance of national policies in shaping urban policy in this area, and suggests how this new wave of urban telematics policies may play an important role in developing a place-based politics for shaping progressive urban change in the new global era.